Strategi Penerapan Warehouse 7S untuk Memaksimalkan Peran Komite 7S di XYZ Mini Sort Hub Bandung - Fajar Iman Hermansyah; Rakhmat Ceha; Ahmad Arif Nurrahman (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. The 7S approach was hampered in its implementation stage, this obstacle was caused by the 7S committee working less than optimally. The warehouse audit results obtained a score of 78.38% of the management target of 95%. The method for analyzing weak 7S variables uses the IPA (Important Performance Analysis) method. This method is based on the results of a questionnaire given to Ninja Xpress employees regarding the performance of the 7S committee. A questionnaire with open questions produces 26 statements of the 7S variable attributes. The 7S attributes were developed into a closed questionnaire. The results of the analysis produce a gap of -0.58, namely that employees really expect cleanliness and tidiness throughout the warehouse which is not fulfilled by the 7S committee. The weak attribute condition is depicted through a Cartesian degree diagram which is the output of the IPA method. The results of the analysis using the IPA method for attribute P6 are in quadrant A, which is the quadrant that must be paid attention to by the 7S committee for improvements. Improvement of weak attributes is carried out using the Six Sigma method. The results of the identification of the company still have many improvements that must be carried out by the 7S committee. The appropriate strategy for improvement steps is to carry out Improve and Control using check sheets that have been designed. Abstrak. Pendekatan 7S mengalami hambatan dalam tahap implementasinya, hambatan ini disebabkan oleh komite 7S yang bekerja kurang maksimal. Hasil audit gudang memperoleh skor 78,38% dari target manajemen sebesar 95%. Metode untuk menganalisis variabel 7S yang lemah menggunakan metode IPA (Important Performance Analysis). Metode ini didasarkan pada hasil kuesioner yang diberikan kepada karyawan Ninja Xpress mengenai kinerja komite 7S. Kuesioner dengan pertanyaan terbuka menghasilkan 26 pernyataan atribut variabel 7S. Atribut-atribut 7S tersebut dikembangkan menjadi kuesioner tertutup. Hasil analisis menghasilkan gap sebesar -0,58 yaitu karyawan sangat mengharapkan kebersihan dan kerapian di seluruh bagian gudang yang tidak dipenuhi oleh komite 7S. Kondisi atribut yang lemah tersebut digambarkan melalui diagram kartesius derajat yang merupakan output dari metode IPA. Hasil analisis dengan menggunakan metode IPA untuk atribut P6 berada pada kuadran A yang merupakan kuadran yang harus diperhatikan oleh panitia 7S untuk dilakukan perbaikan. Perbaikan terhadap atribut yang lemah dilakukan dengan menggunakan metode Six Sigma. Hasil identifikasi perusahaan masih memiliki banyak perbaikan yang harus dilakukan oleh komite 7S. Strategi yang tepat untuk langkah perbaikan adalah dengan melakukan Improve dan Control dengan menggunakan check sheet yang telah dirancang.